RECREATIONAL PRACTICES IN DEVELOPMENT OF A STUDENT'S MOTOR WITH ADHD (Fiep Bulletin - online, 2019)
The Attention Deficit Disorder and Hyperactivity Disorder (ADHD) is caused by a brain dysfunction,which may cause inattention, impulsivity and hyperactivity. Recreation is a tool that explores motor skills, interaction andcooperation among its participants. The aim of this study was to determine whether stimulation through recreational activities canimprove the motor, social and affective aspects in patients with ADHD. The sample for this case report was a fourteen-year-oldindicated by CEAPEM Itapeva - SP. Active recreation was used as a form of stimulation. Motor changes were evaluated by theKTK test (Körperkoordinations Test für Kinder). After application of the test it was observed changes in the coordinative standardparticipant between the start and end times, respectively (53.8 ± 39.4 vs 59.3 ± 39.1; p